Efficiency of storage battery chloride accumulator type - Berger, G. P.; Momyer, H. H. (My University, 1908)
Introduction: The College Storage Battery was purchased from the Electric Storage Battery Co., of Philadelphia, Pa. and was installed in August. 1905. Its rated load is 110 volts, 20 amperes for eight hours or 160 ampere-hours, which would be 17600 watt-hours. The battery has been used by the students for testing work in the laboratory and for some lighting.
Citation: Berger, G. P. and Momyer, H. H. Efficiency of storage battery chloride accumulator type. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Batteries; Lighting; Electricity; Graduating theses; Senior theses; Theses